Occupational Health Problems Among Women Beedi Workers in an Urban- Field Practice Area - A Cross-Sectional Study - Telugu Aparna; M S Aruna (RGUHS National Journal of Public Health)
Background Beedi rolling a major unorganized-sector activity in India primarily employs women and poses significant health risks. Continuous exposure to tobacco dust fumes and harmful compounds like nitrosamines and nicotine leads to various medical conditions including musculoskeletal respiratory neurological eye skin and gynecological disorders.Aims amp Objectives The study aimed to assess the occupational health problems among women Beedi workers and to assess their knowledge and practice regarding safety measures.Methods A community-based cross-sectional study was conducted among 160 women Beedi workers in the urban field practice areas of the tertiary care centre. Data was collected between May and July 2024 using a semi-structured questionnaire by a simple random technique through a face-to-face interview method after obtaining Institutional Ethical Committee clearance and informed consent from study participants. Data was analyzed using SPSS version 25 and expressed in descriptive statistics and a Chi-square test.Results Out of 160 study subjects the most common health problem was musculoskeletal problems in 124 77.5 followed by eye problems in 89 55.6 and respiratory problems in 77 48.1. Only 25 15.6 know about safety measures. Regarding practice only 72 45 wash their hands after Beedi making and none of the subjects wear gloves or masks.Conclusion The most typical health problems among women Beedi workers were musculoskeletal problems and then eye and respiratory problems. They have poor knowledge and practice regarding safety measures.